Stephen Kumalo’s Individuation Process in Alan Paton’s Cry, the Beloved Country: Jungian Psychoanalysis - Daniel Rino Gogani (Universitas Negeri Surabaya, 2025)
This study explores a novel entitled Cry, the Beloved Country by South African writer Alan Paton. The purpose of this study is to analyze the literary work using Carl Gustav Jung's Jungian psychoanalytic approach. By focusing on archetype theory which is reflected in the interaction or social relationship between the main character, Stephen Kumalo and other characters such as, Teophilus Msimangu, James Jarvis, and Absalom Kumalo. In addition, this study also uses individuation theory to analyze Stephen Kumalo by focusing on his traditional and conservative cultural values that confront the modern and urban values of the big city of Johannesburg. The study found that the main character's social relationships with other characters reflect several archetypes such as, Hero, Shadow, Self, Wise Old Men, Father. In addition, Stephen Kumalo's individuation process can also be indicated as successful. It can be seen from how the main character shows a significant change by becoming a more mature, whole, and authentic person.